2023
DOI: 10.3390/f14112247
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metal Elements and Biochemical Constituents of Wild Turkey Tail (Trametes versicolor) Mushrooms Collected from the Shivalik Foothills of the Himalayas, India

Yasser S. Mostafa,
Ivan Širić,
Saad A. M. Alamri
et al.

Abstract: Wild medicinal mushrooms are known to contain significant amounts of essential biochemical compounds with potential health benefits. Therefore, this study aimed to investigate the metal elements and biochemical constituents of wild turkey tail (Trametes versicolor) mushrooms collected from the Shivalik foothills of the Himalayas, India. Mushroom samples were purposefully collected from eleven (11) sampling sites located in three (3) districts of North Indian states (Uttar Pradesh and Uttarakhand). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The basidiomycete T. versicolor is a filamentous fungus that belongs to the white rot fungi and is known for its ability to degrade the complex structure of lignocellulosic biomass thanks to a complex system of enzymes it produces during its growth [17]. T. versicolor can be cultivated on various substrates in a wide temperature range, even between 15 and 32 °C [38,39]. Substrate properties such as particle size and chemical composition have a major influence on the performance of the SSF process, as do numerous parameters such as moisture content, temperature, availability of nutrients and fermentation time [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basidiomycete T. versicolor is a filamentous fungus that belongs to the white rot fungi and is known for its ability to degrade the complex structure of lignocellulosic biomass thanks to a complex system of enzymes it produces during its growth [17]. T. versicolor can be cultivated on various substrates in a wide temperature range, even between 15 and 32 °C [38,39]. Substrate properties such as particle size and chemical composition have a major influence on the performance of the SSF process, as do numerous parameters such as moisture content, temperature, availability of nutrients and fermentation time [40].…”
Section: Resultsmentioning
confidence: 99%
“…Fluctuations in ash content are caused by various metal elements in the substrate that have been absorbed by the fungal mycelium and then transferred to the upper body parts of T. versicolor. Mostafa et al [38] also reported that T. versicolor has an average content of protein of 8.12%-11.06%, fat of 0.93%-1.26% and total ash of 2.42%-3.48%.…”
Section: Ash Crude Proteins and Free Fats Content Determinationmentioning
confidence: 97%
See 1 more Smart Citation
“…The major sources of these metals in aquatic ecosystem are anthropogenic activities, uncontrolled industrialization, and excessive usage of chemicals [ 9 ]. Moreover, excessive used of organic and inorganic fertilizers besides non-managed pesticide application aggravate the situation [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms contain a variety of biologically active ingredients that are beneficial to health, including polysaccharides, vitamins, gamma-aminobutyric acid, ergothioneine and minerals, and hence have formed an integral aspect of the human diet for centuries, both as food and as traditional medicinal supplements ( Hu et al, 2021 ). Other compounds like phenolics ( Atila et al, 2023 ), flavonoids and beta-carotene ( Mostafa et al, 2023 ), amino acids ( Sassine et al, 2021 ), and fatty acids ( Abou Fayssal et al, 2021 , 2023 ) found in mushrooms play major roles in the improvement of antioxidant and cardiovascular properties. Moreover, their global consumption has grown significantly in recent years.…”
Section: Introductionmentioning
confidence: 99%